1996
DOI: 10.1203/00006450-199601000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Neonatal Thyroxine Levels and Neurodevelopmental Outcome at Age 5 and 9 Years in a National Cohort of Very Preterm and/or Very Low Birth Weight Infants

Abstract: Transient neonatal hypothyroxinemia is very common in preterm infants. The literature on the effect of this hypothyroxinemia is, however, controversial, and large or long-term follow-up studies are not available. In a nationwide prospective follow-up study on very preterm and (or) very low birth weight infants (n = 717), we studied the relationship between thyroxine levels in the 1st wk of life and neurodevelopmental outcome at 5 y of age and school performance at 9 y of age. Thyroxine concentrations from filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(91 citation statements)
references
References 21 publications
3
84
0
4
Order By: Relevance
“…Conversely, present clinical and experimental evidence seems to suggest that early and prolonged (until week 24) maternal hypothyroxinemia is a risk factor for impaired foetal brain development (3,22,(24)(25)(26). Moreover, other reports of poor developmental outcome in preterm babies indicate that a normal supply of maternal T 4 continues to have an important protective role after midgestation (27,28). Because of the potential irreversibility of foetal brain damage, we decided arbitrarily to give substitutive L-T 4 treatment to women experiencing IH, in order to ensure FT 4 levels similar to those observed in adequately iodine supplemented women at the same stage of pregnancy.…”
Section: Discussionmentioning
confidence: 79%
“…Conversely, present clinical and experimental evidence seems to suggest that early and prolonged (until week 24) maternal hypothyroxinemia is a risk factor for impaired foetal brain development (3,22,(24)(25)(26). Moreover, other reports of poor developmental outcome in preterm babies indicate that a normal supply of maternal T 4 continues to have an important protective role after midgestation (27,28). Because of the potential irreversibility of foetal brain damage, we decided arbitrarily to give substitutive L-T 4 treatment to women experiencing IH, in order to ensure FT 4 levels similar to those observed in adequately iodine supplemented women at the same stage of pregnancy.…”
Section: Discussionmentioning
confidence: 79%
“…For years their alterations in circulating parameters of thyroid function have been considered an expression of their physiological hypophyseal-pituitarythyroid immaturity or a manifestation of nonthyroidal illness, but 2 recent follow-up studies of 640 PT children up to 5 and 9 yr of age (10) and of 400 premature infants up to 2 yr of age (11) have confirmed that severe hypothyroxinemia plays an important causative role in their frequently impaired mental development and disabling cerebral palsy.…”
mentioning
confidence: 99%
“…19 Consistent with this literature, the low levels of T 4 associated with THOP have been found to be related to neurodevelopmental deficits in children born preterm, such as delayed development of motor, cognitive, language, and educational skills. [20][21][22][23][24] Research to date has predominantly focused on TH levels in the first 2 weeks of life, and in most studies outcome assessments have been limited to infancy and the preschool period. The current study aimed to examine the relationship between fT 4 over the first 6 weeks after VPT birth and cognitive functioning and brain development at age 7 years.…”
mentioning
confidence: 99%